A Distinctive Vision for the Liberal Arts: General Education and the Flourishing of Christian Higher Education. Issue 1 (1st January 2016) - Wells, Cynthia A.
Abstract: This article argues that a coherent and inspired general education program, infused with a deliberate vision of the liberal arts, is crucial to the flourishing of Christian higher education. This article begins by describing the context and status of general education, emphasizing how this element of the educational program falls short in embodying a distinctive mission of Christian higher education. This article then contends that a vibrant vision of general education will be grounded in particular aspects of a liberal arts education that fulfill crucial outcomes of the Christian university, specifically cultivating the formal virtues and fostering meaning and purpose. The article concludes with recommendations for advancing the aims of general education within Christian higher education, highlighting the benefits of a common curriculum and intentional faculty development.